2008
DOI: 10.1086/528712
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Bacteremia due to Pseudomonas aeruginosa with Reduced Susceptibility to Piperacillin-Tazobactam: Implications on the Appropriateness of the Resistance Breakpoint

Abstract: In P. aeruginosa bacteremia due to isolates with reduced piperacillin-tazobactam susceptibility, empirical piperacillin-tazobactam therapy was associated with increased mortality. Additional studies are warranted to examine the appropriateness of the current Clinical Laboratory Standards Institute resistance breakpoint of piperacillin-tazobactam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 13 publications
2
63
2
2
Order By: Relevance
“…A classification and regression tree (CART) analysis conducted in their study revealed that a cefepime MIC of Ն8 mg/liter was associated with increased mortality (58.4% compared to 21.4%, P ϭ 0.001), despite the fact that an MIC of 8 mg/liter was considered susceptible at the time of the study (13). Tam and colleagues (14) evaluated outcomes in patients with Pseudomonas aeruginosa bacteremia with reduced susceptibility (defined as an MIC of 32 to 64 mg/liter) to piperacillin-tazobactam, and the susceptibility breakpoint was Յ64 mg/liter at the time of the study. Among patients with a Pseudomonas bloodstream infection, a higher mortality rate was seen in those treated with piperacillin-tazobactam (MIC, 32 mg/liter or 64 mg/liter) than in those treated with other antipseudomonal agents (85.7% compared to 22.2%; P ϭ 0.004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A classification and regression tree (CART) analysis conducted in their study revealed that a cefepime MIC of Ն8 mg/liter was associated with increased mortality (58.4% compared to 21.4%, P ϭ 0.001), despite the fact that an MIC of 8 mg/liter was considered susceptible at the time of the study (13). Tam and colleagues (14) evaluated outcomes in patients with Pseudomonas aeruginosa bacteremia with reduced susceptibility (defined as an MIC of 32 to 64 mg/liter) to piperacillin-tazobactam, and the susceptibility breakpoint was Յ64 mg/liter at the time of the study. Among patients with a Pseudomonas bloodstream infection, a higher mortality rate was seen in those treated with piperacillin-tazobactam (MIC, 32 mg/liter or 64 mg/liter) than in those treated with other antipseudomonal agents (85.7% compared to 22.2%; P ϭ 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with a Pseudomonas bloodstream infection, a higher mortality rate was seen in those treated with piperacillin-tazobactam (MIC, 32 mg/liter or 64 mg/liter) than in those treated with other antipseudomonal agents (85.7% compared to 22.2%; P ϭ 0.004). (14). Similarly, in patients with Gram-negative bacteremia treated with levofloxacin, DeFife et al reported longer time to clearance of infection (2.1 days compared to 1.0 day, P Ͻ 0.001) and longer length of stay (16.4 days compared to 7.3 days, P ϭ 0.02) for patients in the high-MIC group (defined as 1 mg/liter or 2 mg/liter) than for those with lower MICs, and the susceptibility breakpoint was 2 mg/liter at the time of the study (15).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 To increase fT >MIC by 1 . 26 Control patients received alternative empiric therapy (in doses appropriate for renal function as recommended by the manufacturer) within 24 hours of the first positive blood culture result to which the isolate was found to be susceptible using current CLSI susceptibility breakpoints. Original magnification: 132 Â 93 mm (300 Â 300 DPI).…”
Section: Dosing Strategies To Improve the Probability Of Target Attaimentioning
confidence: 99%
“…The breakpoints are often used, in conjunction with susceptibility results, to predict clinical outcome. However, emerging data highlight the lack of association between in vitro susceptibility breakpoints and outcomes (3,30).Fluoroquinolones are considered to be concentration dependent, with both the area under the concentration-time curve from 0 to 24 h (AUC 0-24 ) divided by the MIC (the AUC 0-24 /MIC ratio) and the maximum serum drug concentration (C max ) divided by the MIC (the C max /MIC ratio) as predictors of clinical outcome (13,24). Numerous studies have attempted to discern the parameter best associated with clinical outcome.…”
mentioning
confidence: 99%
“…The breakpoints are often used, in conjunction with susceptibility results, to predict clinical outcome. However, emerging data highlight the lack of association between in vitro susceptibility breakpoints and outcomes (3,30).…”
mentioning
confidence: 99%